Effects of two endoscopic posterior lumbar interbody fusion surgical sequences for treatment of unstable lumbar spinal stenosis: a retrospective study - Pan, Hengyan; Feng, Ruibing; Duan, Xiaofeng; Huang, Yizheng; Hu, Hao; Wu, Gang; Huang, Yong (Frontiers in Surgery, 2025)
BackgroundEndoscopic posterior lumbar interbody fusion (Endo-PLIF) is commonly employed for the treatment of unstable lumbar spinal stenosis (ULSS). However, the impact of different surgical sequences on clinical outcomes remains unclear. This study aims to compare outcomes between two Endo-PLIF surgical sequences for ULSS.MethodThis retrospective study analyzed ULSS patients who underwent Endo-PLIF at our institution from 2019 to 2023. Group A had guidewire placement before decompression, while Group B had it after. Both groups began with localization and concluded with percutaneous screw fixation. Primary outcomes measured were operative time, fluoroscopy frequency, pedicle screw accuracy (using Gertzbein and Robbins criteria on postoperative CT), and functional scores (VAS, ODI). Fusion rates and complications were also evaluated.ResultGroup A demonstrated significantly shorter operative time and fewer intraoperative fluoroscopies than Group B. Furthermore, pedicle screw placement exhibited a higher rate of excellent/good grades (Gertzbein and Robbins) in Group A. Both groups achieved significant and equivalent improvements in VAS and ODI scores at 1-year follow-up compared to preoperative baselines. Fusion rates and overall complication rates did not differ significantly between the groups.ConclusionsFor patients with ULSS, following the surgical procedure of inserting the guide wire before decompression can lead to more satisfactory clinical outcomes.